2005
DOI: 10.1016/j.polymdegradstab.2004.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stabilisation of poly(vinyl chloride) by organotin compounds

Abstract: The effect of LSN 117 (dioctyl tin bis isooctyl thioglycollate, an organotin compound) on the heat stability of plasticised PVC was investigated in this study. The organotin stabiliser had carbonyl and carboxylate groups and PVC contained traces of Fe, Zn, Ca, Cu and Sn. The heat stability of the films were tested at 140 C and 160 C or 180 C by heating in an air circulation oven up to 2 h and by measuring HCl evolved using a Metrohm 763 PVC thermomat and by thermogravimetric analysis. The onset of HCl evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(51 citation statements)
references
References 9 publications
(6 reference statements)
1
49
0
1
Order By: Relevance
“…3,[6][7][8][9][10] Nevertheless, thermal degradation of PVC is one of the inherent problems associated with the manufacture and use of some polymers. 11 These problems can be minimized by introducing stabilizing additives, which generally contain heavy metals such as cadmium and lead, organotin compounds, 12 phosphites, 13 and calcium and zinc salts. 14,15 But it is shown that the latter ones have less toxicity and so they can be used as heat stabilizers in most applications, especially food packaging and medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…3,[6][7][8][9][10] Nevertheless, thermal degradation of PVC is one of the inherent problems associated with the manufacture and use of some polymers. 11 These problems can be minimized by introducing stabilizing additives, which generally contain heavy metals such as cadmium and lead, organotin compounds, 12 phosphites, 13 and calcium and zinc salts. 14,15 But it is shown that the latter ones have less toxicity and so they can be used as heat stabilizers in most applications, especially food packaging and medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…O desenvolvimento da coloração na superfície das amostras foi atribuído ao conjunto de duplas ligações conjugadas, formadas no processo de degradação térmica (desidrocloração) [53] e as sequências de polienos podem conferir a coloração indesejada ao polímero [54] . As alterações na coloração dos filmes também são atribuídas à colonização dos microrganismos, pela excreção de pigmentos microbiais lipofílicos, caracterizando o processo de biodegradação do polímero [32] .…”
Section: Resultsunclassified
“…The thermal stability of prepared PVC films was determined by the following two methods: thermomat described in detail elsewhere [5,24]. 0.50 g of PVC film cut into about 2.0 mm  2.0 mm size was placed in the reaction vessel.…”
Section: Preparation and Test Of Pvc Filmsmentioning
confidence: 99%
“…(5). ZnSt 2 as the product from such a reaction is another effective thermal stabilizer for PVC, and the other product CaCl 2 does not promote a sudden "zipper dehydrochlorination" as ZnCl 2 does [10].…”
Section: Formulation Stabilized With Cast 2 /Znlmentioning
confidence: 99%